The Inconsistency Effect of Anomalies on the Muslim Eid (Id Fitri) towards Abnormal Return : Case Study in the Indonesia Stock Exchange - Muhammad Abdul Ghoni (AL-FALAH : Journal of Islamic Economics, 2019)
Purposes: The purpose of this paper is to analyze the causes of inconsistency in the effect of the "Anomalies" of the Islamic Eid (Eid al-Fitr) on Abnormal returns on the Indonesia Stock Exchange. Design/Methodology/Approach: This article applied the quatitative analysis. In practise, it consistently uses the descriptive qantitative in measuring the effect cross selected-variables.Findings: Based on the results of the analysis showed that the inconsistency of the effect of "Anomalies" on the Islamic Eid (Eid al-Fitr) on Abnormal returns on the Indonesia Stock Exchange was caused by various things, including behavior of investors caused by uncertainty during the Eid al-Fitr. Originality/Value: a set of novelty identificated from the article is that study deeply measures the relationship between anomalies of The Muslim Eid and Abnomarmal Return in The Indonesia Stock Exchange.